Taj Mahal inscriptions
Arabic and Persian inscriptions from the Taj Mahal copied in the Naskh and Nastalik script in the [19th century] with English translations and commentary.
Handwritten transcripts.
Collection material in Persian, with Arabic and English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Inscriptions, Arabic -- India; Inscriptions, Persian -- India; Taj Mahal (Agra, India)